The Impact of Online Game Addiction on Eye Fatigue in 2020 High School Students in Sibolga City - Rumiris Simatupang (Science Midwifery, 2020)
The very rapid development of technology today has resulted in major changes for society, especially teenagers and students. The development of traditional games has become modern games with the existence of an internet network called Online Games. Data in Indonesia statesThe number of school-age children in 2017 (10.1%) are addicted to Online Games, in Korea 2.4% and 10.2% aged between nine and thirty-nine years, in China 13.7% and in America there are 1.5% to 8.2% who experience addiction3 . Based on the initial survey, it was found that almost all high school students have a cellphone / smartphone device that can access games. This study aims to determine whether there is an impact of online game addiction on eye fatigue in high school students in Sibolga City. This research is a descriptive analytic study. The population in this study were high school students in Sibolga City. Sampling was stratified random sampling. The tool used is a questionnaire.